An electrochemical sensor based on cobalt tetroxide-vinegar residue-derived N-doped porous carbon and its application in dopamine detection
By growing Co3O4 in situ on porous carbon materials derived from vinegar residue, Co3O4/VR-AC-T electrode materials were prepared, and electrochemical sensors were constructed, which solved the problem of insufficient detection range and detection limit in the existing dopamine detection methods, achieved high sensitivity, low cost, and had the characteristics of environmentally friendly carbon recycling.
Patent Information
- Application Number
- CN202411777410.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The existing dopamine detection methods have problems such as insufficient detection range, insufficient detection limit, high cost of sensing materials and complex synthesis process, making it difficult to achieve high sensitivity and low cost mass production.
Using an electrochemical sensor based on tricobalt tetroxide-eukin slag-derived N-doped porous carbon, the electrochemical sensor of a triodeoxygenic system was prepared by growing ZIF-67-derived Co3O4 in situ on the porous carbon material derived from vinegar slag, and mixed with Nafion to coat it on the electrode surface to construct an electrochemical sensor of a triode system.
It realizes high sensitivity detection of dopamine, has a wide linear response range, good stability and reproducibility, and is low in preparation cost, simple in process, suitable for large-scale mass production, and realizes environmentally friendly carbon recycling by utilizing industrial solid waste vinegar residue.
Smart Images

Figure CN119246631B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical sensors, and in particular relates to an electrochemical sensor based on cobalt tetroxide-vinegar residue-derived N-doped porous carbon and an application thereof in dopamine detection. Background Art
[0002] Dopamine (DA) is one of the most important excitatory neurotransmitters in the central nervous system, kidney and hormone system of mammals. Abnormal DA levels can lead to many diseases, such as Parkinson's disease, Alzheimer's disease and schizophrenia. For healthy humans, the content of DA in extracellular fluid is in the range of 0.01-1 μM. When it is too high or too low, it may cause disease or have already produced lesions. On the other hand, dopamine can be used for intravenous injection of drugs to increase the heart rate and blood pressure of the sympathetic nervous system, which may be abused as sports stimulants, clenbuterol, etc. Therefore, the sensitive and selective detection of DA in samples such as serum, urine, blood, brain and spinal cord, and milk is of great significance for physiological function, clinical diagnosis and food safety.
[0003] At present, DA detection methods mainly include high performance liquid chromatography, UV-visible spectrophotometry, fluorescence spectroscopy, capillary electrophoresis and electrochemical methods. The electrochemical method has the advantages of high sensitivity and miniaturization potential, and stands out because of its simple detection process, time saving, friendly operation and low cost. Although electrochemical sensors based on materials such as cobalt, manganese, gold, copper, and graphene have a certain detection sensitivity for DA, their detection range is not good enough and the detection limit needs to be further improved. In addition, most of the sensing materials, i.e., specific detection and recognition components, are quite expensive and the synthesis process is also complicated. It is very important to develop suitable electrochemical sensors, design low-cost materials to achieve high-sensitivity detection of DA, and enable them to be mass-produced. Summary of the invention
[0004] The present application is to provide an electrochemical sensor based on cobalt tetroxide-vinegar residue-derived N-doped porous carbon and its application in dopamine detection. The cobalt tetroxide-vinegar residue-derived N-doped porous carbon has good catalytic activity for dopamine and is suitable as a specific recognition element (electrode material) of a dopamine electrochemical sensor. The modified electrode is a working electrode, which forms a three-electrode system with a selected reference electrode and a counter electrode, and forms an electrochemical sensing platform for detecting dopamine with an electrochemical workstation. The sensor has a wide corresponding response range, good stability and reproducibility, and can achieve highly sensitive recognition and detection of dopamine.
[0005] The present invention is achieved through the following technical solutions:
[0006] An electrochemical sensor based on cobalt tetroxide-vinegar residue-derived N-doped porous carbon, the electrochemical sensor is a three-electrode system, comprising a working electrode, a counter electrode and a reference electrode, the counter electrode is a platinum sheet or a platinum wire, and the reference electrode is a silver / silver chloride electrode whose internal reference solution is a saturated KCl solution; the working electrode is a cobalt tetroxide-vinegar residue-derived N-doped porous carbon modified electrode, the cobalt tetroxide-vinegar residue-derived N-doped porous carbon is obtained by in-situ growing Co3O4 derived from a high-metal organic framework material ZIF-67 on a wrinkled, porous, self-doped nitrogen carbon-based material derived from industrial solid waste vinegar residue.
[0007] The electrochemical sensor constructed by the cobalt tetroxide / vinegar residue-derived N-doped porous carbon modified electrode exhibits good dopamine electrocatalytic activity. The sensor has a wide linear response range, good reproducibility and stability, and can analyze actual biological samples, thereby realizing highly sensitive real-time monitoring of dopamine.
[0008] As some possible implementation methods of the present application, the method for preparing the working electrode comprises the following steps:
[0009] S1. Wash, dry, crush and sieve the industrial solid waste vinegar residue to obtain clean vinegar residue powder; perform high-temperature pyrolysis and carbonization on the vinegar residue powder under argon atmosphere to obtain VR-CT; mix the VR-CT in KOH solution, activate and form pores under nitrogen protection, and then perform natural cooling, centrifugation, washing, drying, grinding and sieving in sequence to obtain VR-AC-T; wherein T is the pyrolysis temperature;
[0010] S2, weighing the VR-AC-T and dispersing it in a cobalt nitrate / methanol solution to prepare a solution 1; weighing 2-methylimidazole and dispersing it in methanol and stirring it thoroughly to prepare a solution 2; slowly pouring the solution 2 into the solution 1, stirring it at a uniform speed, centrifuging, washing, drying, and grinding to obtain a ZIF-67 / VR-AC-T composite; pyrolyzing the ZIF-67 / VR-AC-T composite in argon, cooling it naturally, and then calcining it in an air atmosphere to obtain a Co3O4 / VR-AC-T composite material, i.e., a cobalt-based N-doped porous carbon composite modified electrode;
[0011] S3. The ground Co3O4 / VR-AC-T composite material and Nafion are mixed and dispersed in deionized water, and the Co3O4 / VR-AC-T suspension is obtained after ultrasonic homogenization. Then, it is dropped on the polished GCE surface and naturally dried to obtain the Co3O4 / VR-AC-T composite material modified electrode.
[0012] As some feasible implementation methods of the present application, in step S1, the drying temperature of the industrial solid waste vinegar residue is 60°C, the drying time is 12 h to 24 h, and the sieving mesh number is 100 mesh.
[0013] As some possible implementation methods of the present application, in step S1, the carbonization time is 2 h, the heating rate is 5°C / min, and the carbonization temperature is 600-900°C.
[0014] As some feasible embodiments of the present application, in step S1, the mass ratio of the VR-CT to the potassium hydroxide solution is 10:1, the mass fraction of the potassium hydroxide solution is 10%, the temperature of the potassium hydroxide solution is 80°C; and the activation time is 1 h.
[0015] As some feasible embodiments of the present application, in step S2, the mass ratio of VR-AC-T, Co(NO3)2 in solution one and 2-methylimidazole in solution two is 0.125:0.872:0.986.
[0016] As some possible implementation methods of the present application, in step S2, the uniform stirring time is 12-36 h, the centrifugal speed is 11000 rpm, and the time is 10 min; the washing dispersant used is anhydrous ethanol; and the drying time is 12h-24h.
[0017] As some possible implementation methods of the present application, in step S2, the pyrolysis temperature in the argon atmosphere is 700°C, and the holding time is 2 h; the calcination temperature in the air atmosphere is 150°C-300°C, and the holding time is 12 h.
[0018] As some possible implementation methods of the present application, in step S3, the concentration and ratio of the Co3O4 / VR-AC-T suspension are: the concentration of Co3O4 / VR-AC-T is 1-10 mg / mL, V Nafion :V diH2O =1:24, and the volume added to the polished GCE surface was 1-10 μL.
[0019] In addition, to achieve the above-mentioned purpose, the present invention also provides an application of an electrochemical sensor based on cobalt tetroxide-vinegar residue-derived N-doped porous carbon in dopamine detection.
[0020] Specifically, the dopamine to be tested was dispersed in a pH 7.4 PBS buffer solution, and the constructed electrochemical sensor was used to detect the dopamine test solution in a potential window of -0.1-0.6 V by cyclic voltammetry (CV) and differential pulse voltammetry (DPV), and the corresponding current value was measured; the specific detection and recognition components were screened and optimized according to the magnitude of the current value; the specific detection and recognition components were screened and optimized according to the current value and (scan rate) 1 / 2The electrode reaction process was analyzed based on the linear relationship between the current value and the dopamine concentration; the concentration of the dopamine solution to be tested was calculated based on the linear relationship between the current value and the dopamine concentration; the linear relationship between the dopamine concentration and the current value was I p =0.6337 Con [DA] - 1.5802,R 2 = 0.997; In 100-600 μM DA solution: I p = 0.6337 Con [DA] - 1.5802,R 2 = 0.999.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) In the present invention, ZIF-67-derived Co3O4 is in situ grown on a wrinkled, porous, self-doped nitrogen carbon-based material derived from industrial solid waste vinegar residue to obtain a Co3O4 / VR-AC-T electrode material, which is then mixed with a Nafion aqueous solution and coated on the electrode surface to successfully prepare a Co3O4 / VR-AC-T electrode, which effectively improves the conductivity and dispersibility and greatly improves the catalytic activity of the electrode material.
[0023] (2) The present invention uses Co3O4 / VR-AC-T electrode material to construct a DA electrochemical sensor, which exhibits good catalytic activity for dopamine, and has a wide linear response range, good stability and reproducibility, and can achieve highly sensitive detection of dopamine.
[0024] (3) The preparation cost of the Co3O4 / VR-AC-T-based dopamine electrochemical sensor provided by the present invention is low. The price of cobalt-based reagents is about 0.4458 yuan / g, while the synthetic unit price of VR-AC-T, i.e. the retail price of vinegar residue, is only 0.01436 yuan / g. The process is simple and safe. The preparation of the vinegar residue-derived porous carbon only requires the steps of crushing-carbonization-potassium hydroxide activation, and can achieve self-nitrogen doping, effectively improving the electron transmission efficiency, and can be mass-produced. The acidic solid waste vinegar residue with an annual output of 3 million tons is converted into functional carbon-based materials, achieving self-doping with nitrogen, avoiding the secondary pollution of the soil by the acidic leachate caused by direct landfill, being environmentally friendly, and realizing carbon circulation. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 FeSEM image of Co3O4 / VR-AC-800;
[0026] Figure 2CV graphs of electrodes with different modified materials in 0.1M PBS (pH 7.4) solution saturated with N2 gas containing DA;
[0027] Figure 3 CV graphs of the electrochemical sensor of the present invention at different scanning rates in a 0.1M PBS (pH 7.4) solution saturated with N2 gas containing DA;
[0028] Figure 4 DPV diagrams and linear standard curves of the electrochemical sensor of the present invention in DA solutions of different concentrations;
[0029] Figure 5 It is a reproducibility test and stability test of the electrochemical sensor of the present invention;
[0030] Figure 6 This is the DPV curve of the electrochemical sensor of the present invention for detecting the DA content in human serum. DETAILED DESCRIPTION
[0031] The preparation and detection performance of the electrochemical sensor constructed by Co3O4 / VR-AC-800 modified electrode for detecting dopamine are further described below in conjunction with specific examples.
[0032] Example 1
[0033] (1) Preparation of electrode materials
[0034] The industrial solid waste vinegar residue purchased from a vinegar factory in Jiangsu was washed three times with deionized water and anhydrous ethanol in sequence, dried at 60°C for 24 hours, crushed, and passed through a 100-mesh sieve to obtain clean vinegar residue powder; in a high-purity argon atmosphere, the clean and dry vinegar residue powder was kept at 800°C for 2 hours at a heating rate of 5°C / min in a tube furnace, and ground to obtain VR-C-800;
[0035] 500 mg of the carbonized vinegar residue was dispersed in 50 ml of a 10% hot KOH solution, placed on a constant temperature magnetic stirrer and stirred at a constant speed, kept at 80°C for 1 hour, stopped heating, naturally cooled to room temperature and aged for 24 hours; then centrifuged at 10000 rpm for 10 minutes, the supernatant was removed, and the obtained precipitate was immersed in 1 M HCl for 3 hours to remove excess potassium hydroxide and impurities, and centrifuged and washed with deionized water and ethanol in turn until neutral; finally, the precipitate was placed in an 80°C forced air drying oven for 24 hours, ground, and passed through a 100-mesh sieve to obtain VR-AC-800;
[0036] 30 ml of methanol was measured in a beaker, 872 mg of cobalt nitrate was weighed and placed in the beaker, and the solution was stirred thoroughly to obtain a cobalt nitrate / methanol solution; 125 mg of VR-AC-800 was then added and stirred at a constant speed for 30 min to obtain a uniformly dispersed solution 1; 10 ml of methanol was measured in a beaker, 986 mg of 2-methylimidazole was weighed and dispersed in the methanol and stirred thoroughly to obtain a solution 2; the solution 2 was slowly poured into the solution 1, stirred at a constant speed for 36 h, and then centrifuged at 11000 rpm for 10 min, the supernatant was carefully removed, and the solution was centrifuged and washed 3 times with anhydrous ethanol; the obtained black-purple precipitate was vacuum dried at 60 °C for 12 h, and ground to obtain a ZIF-67 / VR-AC-800 complex.
[0037] The ZIF-67 / VR-AC-800 composite was pyrolyzed at 700°C for 2 h at a heating rate of 5°C / min in high-purity argon, and then ground into powder after natural cooling; the ground powder was then kept at 150°C for 12 h at a heating rate of 5°C / min in an air atmosphere, naturally cooled, and ground into powder to obtain Co3O4 / VR-AC-800.
[0038] (2) Electrode preparation
[0039] 6 mg VR-AC-800 and Co3O4 / VR-AC-800 materials were dispersed in 960 μL diH2O respectively, and 40 μL Nafion was added to prepare 6 mg / mL electrode dispersion; the GCE electrode with an area of 3 mm was polished to a mirror state with 0.3 μm and 0.05 μm alumina polishing powders, and then ultrasonically cleaned with 1 mol / L hydrochloric acid, anhydrous ethanol, and diH2O for 1 min, and dried with N2 gas; 7.5 μL electrode dispersion was slowly dripped on the GCE surface and dried naturally at room temperature to obtain VR-AC-800 electrode and Co3O4 / VR-AC-800 electrode.
[0040] (3) Construction of DA electrochemical sensor
[0041] A three-electrode system was used to connect a CHI 760e electrochemical workstation to construct a DA sensor, with the Co3O4 / VR-AC-800 electrode as the working electrode, the silver / silver chloride electrode as the reference electrode, and the platinum sheet as the counter electrode.
[0042] Comparative Example 1
[0043] (1) VR-AC-600
[0044] The industrial solid waste vinegar residue purchased from a vinegar factory in Jiangsu was washed three times with deionized water and anhydrous ethanol in sequence, dried at 60°C for 24 hours, crushed, and passed through a 100-mesh sieve to obtain clean vinegar residue powder; in a high-purity argon atmosphere, the clean and dry vinegar residue powder was kept at 600°C for 2 hours at a heating rate of 5°C / min in a tube furnace, and ground to obtain VR-C-600;
[0045] 500 mg of the carbonized vinegar residue was dispersed in 50 ml of a 10% hot KOH solution, placed on a constant temperature magnetic stirrer and stirred at a constant speed, kept at 80°C for 1 hour, stopped heating, naturally cooled to room temperature and aged for 24 hours; then centrifuged at 10000 rpm for 10 minutes, the supernatant was removed, and the obtained precipitate was immersed in 1 M HCl for 3 hours to remove excess potassium hydroxide and impurities, and centrifuged and washed with deionized water and ethanol in turn until neutral; finally, the precipitate was placed in an 80°C forced air drying oven for 24 hours, ground, and passed through a 100-mesh sieve to obtain VR-AC-600;
[0046] (2) VR-AC-700
[0047] The industrial solid waste vinegar residue purchased from a vinegar factory in Jiangsu was washed three times with deionized water and anhydrous ethanol in sequence, dried at 60°C for 24 hours, crushed, and passed through a 100-mesh sieve to obtain clean vinegar residue powder; in a high-purity argon atmosphere, the clean and dry vinegar residue powder was kept at 700°C for 2 hours at a heating rate of 5°C / min in a tube furnace, and ground to obtain VR-C-700;
[0048] 500 mg of the carbonized vinegar residue was dispersed in 50 ml of a 10% hot KOH solution, placed on a constant temperature magnetic stirrer and stirred at a constant speed, kept at 80°C for 1 hour, stopped heating, naturally cooled to room temperature and aged for 24 hours; then centrifuged at 10000 rpm for 10 minutes, the supernatant was removed, and the obtained precipitate was immersed in 1 M HCl for 3 hours to remove excess potassium hydroxide and impurities, centrifuged with deionized water and ethanol in turn, and washed to neutrality; finally, the precipitate was placed in an 80°C forced air drying oven for 24 hours, ground, and passed through a 100-mesh sieve to obtain VR-AC-700;
[0049] (3) VR-AC-900
[0050] The industrial solid waste vinegar residue purchased from a vinegar factory in Jiangsu was washed three times with deionized water and anhydrous ethanol in sequence, dried at 60°C for 24 hours, crushed, and passed through a 100-mesh sieve to obtain clean vinegar residue powder; in a high-purity argon atmosphere, the clean and dry vinegar residue powder was kept at 900°C for 2 hours at a heating rate of 5°C / min in a tube furnace, and ground to obtain VR-C-900;
[0051] 500 mg of the carbonized vinegar residue was dispersed in 50 ml of a 10% hot KOH solution, placed on a constant temperature magnetic stirrer and stirred at a constant speed, kept at 80°C for 1 hour, stopped heating, naturally cooled to room temperature and aged for 24 hours; then centrifuged at 10000 rpm for 10 minutes, the supernatant was removed, and the obtained precipitate was immersed in 1 M HCl for 3 hours to remove excess potassium hydroxide and impurities, centrifuged with deionized water and ethanol in turn, and washed to neutrality; finally, the precipitate was placed in an 80°C forced air drying oven for 24 hours, ground, and passed through a 100-mesh sieve to obtain VR-AC-900;
[0052] (4) Electrode preparation
[0053] Disperse 6 mg VR-AC-600, VR-AC-700, and VR-AC-900 materials in 960 μL diH2O, and then add 40 μL Nafion to prepare a 6 mg / mL electrode dispersion. Polish the 3 mm GCE electrode to a mirror surface with 0.3 μm and 0.05 μm alumina polishing powders, then clean it with 1 mol / L hydrochloric acid, anhydrous ethanol, and diH2O ultrasonic cleaning for 1 min, and dry it with N2 gas.
[0054] 7.5 μL of electrode dispersion was slowly dropped onto the GCE surface and dried naturally at room temperature to obtain VR-AC-600 electrode, VR-AC-700 electrode, VR-AC-800 electrode, and VR-AC-900 electrode.
[0055] (5) Construction of DA electrochemical sensor
[0056] A three-electrode system was connected to a CHI 760e electrochemical workstation to construct a DA sensor, with VR-AC-600, VR-AC-700, and VR-AC-900 electrodes as working electrodes, silver / silver chloride electrode as reference electrode, and platinum sheet as counter electrode.
[0057] Comparative Example 2 Preparation of Co3O4 Electrode
[0058] 30 ml of methanol was measured in a beaker, 872 mg of cobalt nitrate was weighed and placed in the beaker, and the solution was fully stirred to obtain a cobalt nitrate / methanol solution (solution one). 10 ml of methanol was measured in a beaker, 986 mg of 2-methylimidazole was weighed and dispersed in the methanol, and the solution was fully stirred to obtain solution two. The solution two was slowly poured into the solution one, and the solution was stirred at a constant speed for 36 hours, and then centrifuged at 11000 rpm for 10 minutes, the supernatant was carefully removed, and the solution was centrifuged and washed three times with anhydrous ethanol. The obtained black-purple precipitate was vacuum dried at 60 °C for 12 hours, and ground to obtain a ZIF-67 complex.
[0059] The ZIF-67 composite was pyrolyzed at 700°C for 2 h at a heating rate of 5°C / min in high-purity argon, and ground into powder after natural cooling; the ground powder was then kept at 150°C for 12 h at a heating rate of 5°C / min in an air atmosphere, naturally cooled, and ground into powder to obtain Co3O4.
[0060] (2) Electrode preparation
[0061] 6 mg Co3O4 material was dispersed in 960 μL diH2O, and 40 μL Nafion was added to prepare a 6 mg / mL electrode dispersion. The GCE electrode with an area of 3 mm was polished to a mirror state with 0.3 μm and 0.05 μm alumina polishing powders, and then ultrasonically cleaned with 1 mol / L hydrochloric acid, anhydrous ethanol, and diH2O for 1 min, and dried with N2 gas. 7.5 μL of the electrode dispersion was slowly dripped on the GCE surface and dried naturally at room temperature to obtain a Co3O4 electrode.
[0062] (3) Construction of DA electrochemical sensor
[0063] A three-electrode system was connected to a CHI 760e electrochemical workstation to construct a DA sensor, with the Co3O4 electrode as the working electrode, the silver / silver chloride electrode as the reference electrode, and the platinum sheet as the counter electrode.
[0064] Test Example 1
[0065] Based on Example 1, Co3O4 / VR-AC-800 was characterized by FeSEM and the surface morphology of the electrode material was analyzed. The results are as follows Figure 1 shown.
[0066] from Figure 1It can be seen that the rich convex wrinkled porous structure on the surface of VR-AC-800 gives the material good mass transfer ability, ensuring full adsorption of the biological target molecules to be detected and ensuring full contact with the electrocatalyst Co3O4. At the same time, the Co3O4 particles are relatively evenly distributed on the surface of VR-AC-800, ensuring full exposure of the catalytic active sites.
[0067] Test Example 2 Cyclic Voltammetry
[0068] Based on Example 1, Comparative Example 1, Comparative Example 2, Figure 2 The CV curves of dopamine sensors constructed with different modified electrodes at a scan rate of 50 mv / s in dopamine solutions with the same concentration are given; Figure 2 The CV curves of the dopamine sensor constructed based on Co3O4 / VR-AC-800 electrode at different scan rates in dopamine solutions of the same concentration are given; its CV scanning potential window is -0.1-0.6V, and the electrolyte is 0.1 mol / L PBS buffer solution with a pH of 7.4.
[0069] Depend on Figure 2 It can be seen that GCE has no obvious catalytic activity for dopamine, and its CV curve does not show an obvious response current. Under the same conditions, VR-AC-600, VR-AC-700, VR-AC-800, and VR-AC-900 show stronger redox currents, indicating that vinegar residue-derived nitrogen-doped porous carbon has good catalytic activity for dopamine, and VR-AC-800 shows the best catalytic activity, which can be used as a carbon-based special response element for dopamine sensors.
[0070] It is worth noting that compared with pure VR-AC-800 and Co3O4, the redox current of Co3O4 / VR-AC-800 composite electrode material is the largest, indicating that Co3O4 in the composite material maintains good dopamine catalytic activity and produces synergistic catalytic performance improvement when combined with VR-AC-800.
[0071] Further, by Figure 3 It can be seen that as the scanning speed increases, the cathode peak current and the anode peak current increase successively. pa =14.41 v 1 / 2 - 6.76(R 2 = 0.996), I pc = -12.68 v 1 / 2 + 23.90(R 2= 0.997), and the change of redox peak current is proportional to the square root of the scan rate, indicating that the electron transfer on the Co3O4 / VR-AC-800 electrode is very fast, which is a typical diffusion-controlled process.
[0072] Test Example 3 Differential Pulse Voltammetry
[0073] Based on Example 1, Figure 4 DPV diagrams and linear standard curves of the electrochemical sensor of the present invention in DA solutions of different concentrations; Figure 5 This is a reproducibility test and stability test of the electrochemical sensor of the present invention. Figure 4 a shows the DPV curve of the dopamine sensor constructed by Co3O4 / VR-AC-800 modified electrode in dopamine solutions with different concentrations; Figure 4 b in the figure is the linear relationship between the DPV curve response current and dopamine concentration; Figure 5 a in the figure is the comparison of the response current of dopamine sensors constructed with different batches of Co3O4 / VR-AC-800 modified electrodes to the same concentration of dopamine; Figure 5 b is the response current comparison of the dopamine sensor constructed by Co3O4 / VR-AC-800 modified electrode after storage at room temperature for different time periods, where Figure 5 In the figure, the lines at the top of the histograms drawn in a and b are the error values; Figure 6 DPV curve of dopamine sensor constructed for Co3O4 / VR-AC-800 modified electrode to detect dopamine in actual biological samples. The DPV parameters in this test are: amplitude of 50mV, potential increment of 4mV, pulse width of 0.1s, sampling amplitude of 16.7ms, and pulse of 0.5s.
[0074] like Figure 4 As shown in a and b, as the dopamine concentration increases, the peak current gradually increases. The calculation of three independent experimental data shows that when the dopamine concentration ranges from 0-37.5 μM and 100-800 μM, the oxidation current value shows a good linear relationship with its concentration (0-37.5 μM DA: I p = 0.6337 Con [DA] - 1.5802,R 2 = 0.997; 100-600 μM DA:I p = 0.6337 Con [DA] - 1.5802,R 2 = 0.999). The lowest detection limit (LOD) of the DA sensor device was calculated to be 10 nM by 3 times the noise.
[0075] Furthermore, the reproducibility and stability of the sensor are important indicators of whether it can be industrialized.
[0076] like Figure 5 As shown in a, there is no significant difference in the response current values of dopamine sensors constructed by Co3O4 / VR-AC-800 modified electrodes to the same concentration of DA in 5 batches (three electrodes were tested in each batch). More importantly, the response current value of the sensor constructed by the present invention to dopamine still remained 80% after being placed at room temperature for 13 weeks.
[0077] The above results show that the dopamine sensor constructed with Co3O4 / VR-AC-800 modified electrode has good reproducibility and stability.
[0078] Further, combined with Figure 6 It can be seen that after adding different concentrations of dopamine to human serum using the spike method, the dopamine sensor constructed with the Co3O4 / VR-AC-800 modified electrode can be successfully detected, bringing the peak current into I p =0.6337 Con [DA] - 1.5802, the concentrations were calculated to be 4 μM, 5 μM, and 10 μM, and the recovery was calculated to be 98.6% by comparing the spiked concentrations and the dopamine concentration detected by the sensor. The recovery result was satisfactory.
Claims
1. An electrochemical sensor based on cobalt tetroxide-vinegar residue-derived N-doped porous carbon, comprising a working electrode, a counter electrode and a reference electrode; characterized in that: The working electrode is a cobalt tetroxide-vinegar residue-derived N-doped porous carbon modified electrode, wherein the cobalt tetroxide-vinegar residue-derived N-doped porous carbon is obtained by in-situ growing Co3O4 derived from a high metal organic framework material ZIF-67 on a wrinkled porous, self-doped nitrogen carbon-based material derived from industrial solid waste vinegar residue; The method for preparing the working electrode comprises the following steps: S1. Washing, drying, crushing and sieving industrial solid waste vinegar residue to obtain clean vinegar residue powder; performing high-temperature pyrolysis and carbonization on the vinegar residue powder under an argon atmosphere to obtain VR-CT; The VR-CT is mixed in a KOH solution and activated under nitrogen protection, and then naturally cooled, centrifuged, washed, dried, ground, and sieved in sequence to obtain VR-AC-T; wherein T is the pyrolysis temperature; S2, weighing the VR-AC-T and dispersing it in a cobalt nitrate / methanol solution to prepare a solution 1; weighing 2-methylimidazole and dispersing it in methanol and stirring it thoroughly to prepare a solution 2; slowly pouring the solution 2 into the solution 1, stirring it at a uniform speed, centrifuging, washing, drying, and grinding to obtain a ZIF-67 / VR-AC-T composite; pyrolyzing the ZIF-67 / VR-AC-T composite in argon, cooling it naturally, and then calcining it in an air atmosphere to obtain a Co3O4 / VR-AC-T composite material, i.e., a cobalt-based N-doped porous carbon composite material; S3. The ground Co3O4 / VR-AC-T composite material and Nafion are mixed and dispersed in deionized water, and the Co3O4 / VR-AC-T suspension is obtained after ultrasonic homogenization. Then, it is dropped on the polished GCE surface and naturally dried to obtain the Co3O4 / VR-AC-T composite material modified electrode.
2. The electrochemical sensor based on cobalt tetroxide-vinegar residue derived N-doped porous carbon according to claim 1, characterized in that: In step S1, the carbonization time is 2 hours, the heating rate is 5°C / min, and the carbonization temperature is 600-900°C.
3. The electrochemical sensor based on cobalt tetroxide-vinegar residue derived N-doped porous carbon according to claim 1, characterized in that: In step S1, the mass ratio of the VR-CT to the potassium hydroxide solution is 10:1, the mass fraction of the potassium hydroxide solution is 10%, the temperature of the potassium hydroxide solution is 80° C., and the activation time is 1 hour.
4. The electrochemical sensor based on cobalt tetroxide-vinegar residue derived N-doped porous carbon according to claim 1, characterized in that: In step S2, the mass ratio of VR-AC-T, Co(NO3)2 in solution one and 2-methylimidazole in solution two is 0.125:0.872:0.
986.
5. The electrochemical sensor based on cobalt tetroxide-vinegar residue derived N-doped porous carbon according to claim 1, characterized in that: In step S2, the uniform stirring time is 12-36 h, the centrifugal speed is 11000 rpm, and the time is 10 min; the washing dispersant used is anhydrous ethanol; and the drying time is 12 h~24 h.
6. The electrochemical sensor based on cobalt tetroxide-vinegar residue derived N-doped porous carbon according to claim 1, characterized in that: In step S2, the pyrolysis temperature in the argon atmosphere is 700°C, and the holding time is 2 h; the calcination temperature in the air atmosphere is 150°C-300°C, and the holding time is 12 h.
7. The electrochemical sensor based on cobalt tetroxide-vinegar residue derived N-doped porous carbon according to claim 1, characterized in that: In step S3, the concentration and ratio of the Co3O4 / VR-AC-T suspension are: the concentration of Co3O4 / VR-AC-T is 1-10 mg / mL, V Nafion :V diH2O =1:24, and the volume added to the polished GCE surface was 1-10 μL.
8. The use of an electrochemical sensor based on cobalt tetroxide-vinegar residue derived N-doped porous carbon in dopamine detection according to claim 1, characterized in that: The dopamine to be tested was dispersed in pH 7.4 PBS buffer solution. The constructed electrochemical sensor was used to detect the dopamine test solution in the -0.1-0.6 V potential window by cyclic voltammetry and differential pulse voltammetry to measure the corresponding current value. The specific detection and recognition components were screened and optimized according to the current value. The specific detection and recognition components were screened according to the current value and the scanning rate. 1 / 2 The electrode reaction process was analyzed based on the linear relationship between the current value and the dopamine concentration; the concentration of the dopamine solution to be tested was calculated based on the linear relationship between the current value and the dopamine concentration; the linear relationship between the dopamine concentration and the current value was: in the 0-37.5 μM DA solution, I p = 0.6337 Con [DA] - 1.5802,R 2 = 0.997; In 100 -600 μM DA solution: I p =0.6337 Con [DA] - 1.5802,R 2 = 0.999.
Citation Information
Patent Citations
Cobalt-based modified industrial solid waste vinegar residue derived carbon composite material as well as preparation method and application thereof
CN119176587A